2013
DOI: 10.3906/bot-1210-45
|View full text |Cite
|
Sign up to set email alerts
|

Inula tuzgoluensis (Asteraceae), a new species from Central Anatolia, Turkey

Abstract: The new species Inula tuzgoluensis M.Öztürk & O.Çetin (Asteraceae) is described from Central Turkey. The species grows on salty marshes, in the Cihanbeyli District of Konya Province. Inula tuzgoluensis, an endemic confined to Central Anatolia, is related to I. aucheriana DC. The new species is distinct from the closely allied I. aucheriana by habitus, indumentums, leaves, flowers, pollen grains, and achenes. Photos of the new species are provided. Special attention is also given to its ecology and conservation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Turkey is one of the richest countries in the world in terms of flora and new Turkish species were added in 2013 and 2014 (Öztürk and Çetin, 2013;Karaman Erkul and Aytaç, 2013a;Koç and Aksoy, 2013;Uzunhisarcıklı et al, 2013;Sağıroğlu and Akgül, 2014). In addition to this, there are revisions of some genera from Turkey (Yıldız and Çırpıcı, 2013;Karaman Erkul and Aytaç, 2013b;Akan and Aytaç, 2014).…”
mentioning
confidence: 99%
“…Turkey is one of the richest countries in the world in terms of flora and new Turkish species were added in 2013 and 2014 (Öztürk and Çetin, 2013;Karaman Erkul and Aytaç, 2013a;Koç and Aksoy, 2013;Uzunhisarcıklı et al, 2013;Sağıroğlu and Akgül, 2014). In addition to this, there are revisions of some genera from Turkey (Yıldız and Çırpıcı, 2013;Karaman Erkul and Aytaç, 2013b;Akan and Aytaç, 2014).…”
mentioning
confidence: 99%
“…Autoecological studies on economically important plants in Anatolia, which has a rich vegetation cover thanks to its geographical location and climate, are of great significance in order to understand the growth conditions and effective use of these plants (Çelik et al, 2004;Paksoy et al, 2006). The Asteraceae family, which is known to have the greatest number of species in the world, consists of approximately 23000 species and 1535 genera (Öztürk and Çetin, 2013;Nylinder and Anderberg, 2015). It has been reported that a large number of species of the Asteraceae family, expanding widely over the world and in Anatolia, show pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Asperula L. belongs to Rubiaceae family and contains around 200 species distributed worldwide. It is represented by 41 species in the flora of Turkey with an endemism rate of 49% . Asperula involucrata Wahlenb .…”
Section: Introductionmentioning
confidence: 99%